2012
DOI: 10.1038/cddis.2012.16
|View full text |Cite|
|
Sign up to set email alerts
|

Raf kinases mediate the phosphorylation of eukaryotic translation elongation factor 1A and regulate its stability in eukaryotic cells

Abstract: We identified eukaryotic translation elongation factor 1A (eEF1A) Raf-mediated phosphorylation sites and defined their role in the regulation of eEF1A half-life and of apoptosis of human cancer cells. Mass spectrometry identified in vitro S21 and T88 as phosphorylation sites mediated by B-Raf but not C-Raf on eEF1A1 whereas S21 was phosphorylated on eEF1A2 by both B- and C-Raf. Interestingly, S21 belongs to the first eEF1A GTP/GDP-binding consensus sequence. Phosphorylation of S21 was strongly enhanced when bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…eEF1A1 and eEF1A2 were phosphorylated in vitro by B-Raf and C-Raf on S21, while T88 phosphorylation, observed only on eEF1A1, suggested that this post-translational modification was due to structural differences between the two isoforms. In addition, S21 phosphorylation of eEF1A by C-Raf required the presence of both eEF1A isoforms [24]. On the basis of these findings, we proposed that the formation in cancer cells of a possible heterodimer allowed eEF1A phosphorylation (S21) and this event might represents a switch from the canonical (protein synthesis) to non-canonical (such as tumorigenesis) functions of eEF1A.…”
Section: Introductionmentioning
confidence: 80%
“…eEF1A1 and eEF1A2 were phosphorylated in vitro by B-Raf and C-Raf on S21, while T88 phosphorylation, observed only on eEF1A1, suggested that this post-translational modification was due to structural differences between the two isoforms. In addition, S21 phosphorylation of eEF1A by C-Raf required the presence of both eEF1A isoforms [24]. On the basis of these findings, we proposed that the formation in cancer cells of a possible heterodimer allowed eEF1A phosphorylation (S21) and this event might represents a switch from the canonical (protein synthesis) to non-canonical (such as tumorigenesis) functions of eEF1A.…”
Section: Introductionmentioning
confidence: 80%
“…Although eEF1A2 maps on chromosome 20q13, a region suspected to harbor oncogenes and related to gene amplification in many tumors, Anand et al and Grassi et al reported that overexpression of eEF1A2 did not completely depend on the genomic status of this locus (Anand et al 2002;Grassi et al 2007), suggesting the existence of alternative mechanisms. Furthermore, phosphorylation and expression of eEF1A2 were reported to be modulated by Raf, an important oncogene involved in the Ras/Raf/ERK1/2 signaling pathway (Lamberti et al 2007;Olson and Hallahan 2004;Sanges et al 2012). Besides, the molecular mechanisms of the association of eEF1A2 overexpression with patients' prognosis were also far from elucidation.…”
Section: Fig 3 Continuedmentioning
confidence: 99%
“…Further analyzed, phosphoThr88 seems to stabilize the elongation complex in vivo . In contrast, the phosphorylation of Ser21 -residue that belongs to the first GTP/GDP-binding consensus sequence (G14HVDSGKST in both eEF1A1 and eEF1A2) -could potentially prevent the binding of eEF1A to guanine nucleotides, thus allowing a switch of eEF1A activity from protein biosynthesis to different non-canonical functions (74) . These findings are also supported by other evidence.…”
Section: Raf Kinases and Protein Synthesis Machinerymentioning
confidence: 99%
“…7 -8 eEF1A1 overexpressed in COS7 cells. Phosphorylated eEF1As isolated by SDS-PAGE were then analyzed by mass spectrometry for the presence of phosphopeptides (Sanges et al 2012) (74) .…”
Section: Eef1a Substratementioning
confidence: 99%